State of the environment in the Norwegian, Finnish and Russian border area - Stebel, Kerstin; Christiansen, Guttorm; Derome, John; Grekelä, Ilona (Lapland Regional Environment Centre, 2013)
The main threat to aquatic and terrestrial environments in the joint Norwegian, Finnish and Russian border area is the neighbouring Pechenganikel industrial complex, located on the Kola Peninsula in NW Russia. Emissions from the complex comprise extremely high levels of sulphur dioxide, and particulate material containing a wide range of toxic heavy metals, primarily copper and nickel. The aim of the report is to give an overall view of the current state of the environment, and on changes that have taken place in recent years, in the border area, primarily in the Paz River basin. This publication includes summarized information about air quality and deposition, water quality and the state of aquatic ecosystems in the Inari-Paz watercourse and a number of small lakes, as well as the state of terrestrial ecosystems. In addition, the report presents specific recommendations for future monitoring activities in the Norwegian, Finnish and Russian border area. The results of the studies carried out in this project, as well as the results of earlier national monitoring and scientific research projects, were used to develop a joint monitoring programme for the three countries. There are signs of a slight recovery in the condition of aquatic and terrestrial ecosystems in some parts of the area due to the reduction of sulphur dioxide emissions from the smelters during the past two decades. However, the sulphur dioxide and heavy metal emissions are still excessive and are continuing to have major effects on the environment. The impact of sulphur deposition was clearly evident up to tens of kilometres from the smelters. Even though heavy metal concentrations in many of the plant and aquatic components of the ecosystems decrease relatively sharply with increasing distance from the smelters, the accumulation of pollutants in the ecosystems is continuing. The effects of emissions from the Pechenganikel are most clearly evident in the Paz watercourse, which receives pollutants through the direct discharge of wastewater from the ...